Identification and Characterization of DcUSAGT1, a UDP-Glucose: Sinapic Acid Glucosyltransferase from Purple Carrot Taproots. - Yi-Yun Chen; Zhi-Sheng Xu; Ai-Sheng Xiong (PLoS ONE, 2016)
Purple carrots accumulate abundant cyanidin-based anthocyanins in taproots. UDP-glucose: sinapic acid glucosyltransferase (USAGT) can transfer the glucose moiety to the carboxyl group of sinapic acid thereby forming the ester bond between the carboxyl-C and the C1 of glucose (1-O-sinapoylglucose). 1-O-sinapoylglucose can serve as an acyl donor in acylation of anthocyanins and generate cyanidin 3-xylosyl (sinapoylglucosyl) galactoside in purple carrots. This final product helps stabilize the accumulation of anthocyanins. In this study, a gene named DcUSAGT1 encoding USAGT was cloned from 'Deep purple' carrot taproots. Enzymatic activity was determined using high performance liquid chromatography (HPLC). The optimal temperature and pH value were 30°C and 7.0, respectively. Kinetic analysis suggested a Km (sinapic acid) of 0.59 mM. Expression profiles of DcUSAGT1 showed high expression levels in the taproots of all the three purple carrot cultivars but low expression levels in those of non-purple carrot cultivars. The USAGT activity of different carrots in vitro indicated that crude enzyme extracted from the purple carrot taproots rather than non-purple carrot taproots exhibited USAGT activity. These results indicated that DcUSAGT1 may influence anthocyanin biosynthesis of purple carrot taproots.